Knowledge, Attitudes and Practices of Female College Students Regarding Environment - Malik, Nazma (Nurture, 2020)
The main aim of the study was to assess the knowledge, attitude and practices related to environment particularly among the female college students from first year and fourth year BS Home Economics. Both quantitative and qualitative questions were included. 100 students were given the questionnaires online, comprising of both open and close ended questions related to environmental and water issues. Their responses showed a varying degree of Knowledge, attitudes and practices regarding these environmental issues. There was a significant difference in the reported practices according to grade level of the students. A higher proportion of first year students reported practices following environmental friendly practices as compared to fourth year students. Overall only 58% had a view that environment affects our health. These findings indicate a dire need for raising awareness about the role of environment in human wellness and strategies for inculcating environment friendly habits.